Water Quality Integrated Monitoring System: Employing Arduino Technology for Multiparametric Assessment - K. S. Raghavendra Reddy,; S. Shafiulla Basha,; B. P. Santosh Kumar,; M. Chiranjeevi,; M. Kavya,; U. Rajesh,; M. Hari Kiran Kumar, (International Journal of Scientific Research in Science and Technology, 2024)
The development and deployment of a multiparametric water quality monitoring system utilizing Arduino technology represent a significant advancement in the real-time assessment and management of water resources. This integrated system comprises sensors for Total Dissolved Solids (TDS), Dissolved Oxygen (DO), Electrical Conductivity (EC), Turbidity, pH, and Moisture, enabling continuous and simultaneous monitoring of critical physicochemical variables essential for assessing water quality comprehensively. Leveraging the Arduino platform facilitates efficient data collection and processing, while integration with the IoT Blynk app enables stakeholders to remotely access and monitor water quality metrics in real time. This innovative approach not only enables early detection of anomalies, pollution events, or changes in water quality parameters but also supports timely intervention and sustainable water resource management, thus ensuring safe and sustainable water sources for both human consumption and ecosystem health. By providing constant updates on water health status through the Blynk app, this monitoring system enhances accessibility, awareness, and decision-making processes related to water quality management. The ability to visualize and analyze data remotely empowers stakeholders to make informed decisions promptly, thereby contributing to the overarching goal of safeguarding water sources. This system's comprehensive monitoring capabilities, coupled with its remote accessibility and real-time data visualization features, position it as a vital tool in addressing water quality challenges and promoting sustainable water resource management practices.
Keywords: Blynk App; IOT; Turbidity Sensor; PH sensor; TDS sensor; DO; DHT; EC; Water Quality Monitoring